Birth Rate and Fertility: Knowledge and Expectations Analysis of 3585 University Students - Machado, Maria do Céu; Alves, Maria Isabel; Couceiro, Luísa; Silva, Francisco Goiana da; Morais de Almeida, Miguel; Alves, Isa (Acta Médica Portuguesa, 2014)
Introduction: Nowadays, Portuguese birth rate is insufficient to ensure renewal of generations. Women high education levels and labor market integration and increased economic difficulties are some of multiple factors leading to a delay in average parenting age and an increase of infertility; also subject to others such as obesity, smoking and alcohol consumption. Material and Methods: Transversal epidemiological study, analytical, uncontrolled, from self-filled online questionnaires, promoted by students’ university unions. A sample of 3585 university students was considered and a global and by gender statistic analysis was done through SPSS, Excel was used to build graphics and tables and ArcMap to represent maps. Results: Mainly students from the Health Sciences (40.6%), Universidade de Lisboa (59.4%), female (76.9%), median age of 22; intention to marry/ union 71.0%, parenthood 85.7%. A total of 18.4% smoke, 22.3% consume alcohol and obesity 15.4%; employment (47.4%) and the partner’s will (39.9%) were important determinants for parenthood decision as well as having financial stability to provide a good education (33.6%) and healthcare (38.6%); A total of 53.6% have considered the hypothesis of infertility and highlight above 35 year old maternal age (18.7%), obesity (18%) and female smoking (19.0) as factors. Higher and more significant values for smoking (p = 0.001) and alcohol consumption (p = 0.000) in males were found. Discussion: The sample seems representative, well distributed among different areas of study, with more female respondents than the university portuguese ratio. There are more students with parenting projects than marriage/cohabitation, in accordance with Portuguese data. Nevertheless, the same students identify the family as a priority in comparison with employment and career. Parenting decisions are tied by social-economic situation but an important factor is the low fertility due to the maternal age delay of the first pregnancy. Conclusion: University student unions are an excellent instrument to access them; a high number of respondents consider having children but delay the decision; there is a lack of information about the consequences of delaying parenting age and about infertility factors. The negative trend of fertility must be seen as a necessity to develop specific policies. Keywords: Birth Rate; Students; Universities; Fertility; Portugal.